Study on the performance of cement stabilized limestone tailings blending macadam in pavement base - Li, Wenwei; Zheng, Chunyu; Liu, Chenxu; Zhang, Zhixiong; Wang, Zhen; Wang, Quan (Frontiers in Materials, 2025)
Limestone tailings, a significant solid waste generated during cement manufacturing, face challenges of low recycling efficiency and limited engineering application, representing an underutilized resource. This study systematically evaluated the viability of substituting natural aggregates with limestone tailings in base course composites. Four replacement ratios (0%, 20%, 40%, 60%) were investigated through an integrated experimental approach. A comprehensive assessment framework was established, encompassing mechanical tests (compressive and flexural strength), durability evaluations (drying shrinkage, thermal shrinkage, freeze-thaw resistance, erosion stability), XRD phase analysis, and SEM microstructural imaging. Results indicate that limestone tailings micro-particles exhibit a nucleation effect, and their alkaline components, such as calcium oxide, promote cement hydration. Mixture performance exhibited an initial improvement followed by a decline as the tailings content increased. At a 20% cement-tailings content, the composite demonstrated optimal performance: a 10% increase in 90-day compressive strength, a freeze-thaw resistance coefficient exceeding 80%, enhanced resistance to drying and thermal shrinkage, and superior erosion stability compared to the control group mixture. This study demonstrates that partial replacement of natural aggregates with limestone tailings (specifically at 20%) conserves natural resources and enhances key road performance characteristics. The findings provide crucial evidence supporting the resource utilization of limestone tailings in sustainable road construction.